Polyethylene/(organo-montmorillonite) composites modified with ethylene/methacrylic acid copolymer: Morphology and mechanical properties - Pettarin, Valeria (2008)
Several composites based on high-density polyethylene (PE), organically modified montmorillonite (OMMT) and ethylene/methacrylic acid copolymer (EMAA) were prepared by melt compounding. Three Na+-montmorillonites (MMT) of different precedence were modified with hexadecyl trimethyl ammonium chloride in order to change their nature from hydrophilic to organophilic. The composites morphology was examined by XRD, SEM and TEM. Mechanical properties were evaluated under static conditions. A slight reinforcement was achieved only when OMMT was added to PE. When EMAA was added to the composites, it negatively interacted with OMMT, diminishing the interlayer distance of OMMT, changing the composite morphology, as if OMMT was not present in composites, and deteriorating their mechanical properties. © 2008 Elsevier Ltd. All rights reserved.